The Effect of Losing and Winning on Cheating and Effort in Repeated Competitions - Sarah Necker; Fabian Paetzel (Center for Economic Studies and ifo Institute (CESifo), 2022)
Competitive rewards are often assigned on a regular basis, e.g., in annual salary negotiations or employee-of-the-month schemes. The repetition of competitions can imply that opponents are matched based on earlier outcomes. Using a real-effort experiment, we examine how cheating and effort evolve in two rounds of competitions in which subjects compete with different types of opponents in the second round (random/based on first-round outcome). We find that (i) losing causes competitors to increase cheating in the second round while winning implies a tendency to reduce cheating. A similar effect is found with regard to effort, which losers increase to a larger extent than winners. (ii) Competitor matching does not significantly affect behavior.
Keywords: C91; C92; M52; J28; J33; 330; cheating; effort; competition; competitor; social recognition; laboratory experiment